Design and Analysis of Walking device of Multi-function Ecological Planting Grass Cart. (1st March 2023) - Qi, Xuemei; Wu, Yunjie; Zhang, Jian; Wang, Yuhao
Abstract: Aiming at the problems of complex structure and difficult control of the walking device of the grass planting cart, a walking device of the ecological grass planting cart was designed, including the frame, walking wheel, profile device, depth limiting device, etc. The device limits the depth of three blocks and simulates the shape of the working ground. From the perspective of the soil contact force field and displacement field, EDEM software was used to simulate the discrete elements of the driving wheel and soil suppression effect. It can be seen from the analysis results that the driving wheel has a good suppression effect on soil particles. The depth-limiting effect of the walking device is simulated, and the results show that the distribution area and depth of the contact force field between the three-gear trench device and soil particles are different, and the depth-limiting effect is good.